RECREATIONAL USE OF PREGABALIN IN UKRAINE: AVAILABILITY, PATTERNS OF USE, AND APPLICATION IN CHEMSEX - Lapin, Mykyta; Shevchenko, Maryna (Eastern Ukrainian Medical Journal, 2026)
Introduction: Substance use disorders lead to public health and social problems. Reports about the addictive potential of pregabalin appeared immediately after the drug's launch in 2005. Subsequently, the prevalence of pregabalin abuse in countries around the world began to increase.Methods: The inclusion criterion for the study was recreational use of pregabalin at the time of the study or a history of such use. The sample was formed by the snowball sampling method, data collection was conducted through semi-structured interviews, and analysis was performed using the phenomenological method. The Drugs Wheel model was used to classify psychoactive substances.Results: Substance users are not aware of the risks of recreational use of pregabalin. Pregabalin is available for recreational use in Ukraine through over-the-counter pharmacies. Patterns of recreational use of pregabalin in Ukraine are dangerous in terms of mental and physical health disorders and negative socioeconomic consequences. Pregabalin is used as a tool for chemsex, and users neglect harm reduction measures for risky sexual behavior during such contacts. The difficulty of quitting recreational pregabalin use has been documented, and adherence to the existing mental health care system is low.Discussion: Low awareness of the risks of recreational use of pregabalin among substance users creates a need for educational activities among target groups. Given the commitment of doctors to prescribing pregabalin and the lack of warnings about the negative consequences, it is imperative to educate healthcare professionals about the risks of such prescriptions. Since pregabalin is used as a tool for chemsex, and users neglect harm reduction measures for such contacts, it is advisable to provide them with access to harm reduction measures for risky sexual behavior. Given the difficulty of quitting recreational pregabalin use and the low adherence of substance users to the existing mental health care system, it is recommended to improve this system and introduce harm reduction programs.